(untitled) (Editora Impacto Científico, 2025)
This article investigates the structural and optical behavior of binary blends formed by combining high alumina clay residue (HAAW) and cassava starch (Manihot esculenta Crantz) (AMM), subjected to different heat treatment temperatures. X-ray diffraction (XRD) and colorimetry analyses revealed that, while AMM degrades and carbonizes after 400 °C, RAAA undergoes significant mineralogical transitions, with the formation of hematite and refractory phases. The RAAA+AMM blend showed greater chromatic variation and stability at 800 °C, demonstrating the synergy between the inorganic matrix and the biopolymer. The results point to the potential of natural hybrid pigments, with the RAAA+AMM blend calcined at 800 °C standing out as the most promising system.